2013
DOI: 10.2319/120712-925.1
|View full text |Cite
|
Sign up to set email alerts
|

Photographic assessment of cephalometric measurements

Abstract: Objective: To investigate the relationship between craniofacial measurements obtained from cephalometric radiographs and analogous measurements from profile photographs. Materials and Methods: Lateral cephalograms and standardized facial profile photographs were obtained from a sample of 123 subjects (65 girls, 58 boys; age 7-12 years). Intraclass correlation coefficients (ICCs) were calculated from repeated photographic measurements to evaluate method reliability. Analogous cephalometric and photographic meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
0
22
1
1
Order By: Relevance
“…Similar to our study, when comparing the results of FMA and cephalometric Sn-GoMe, the researchers did not find a strong correlation coefficient. On the contrary, powerful relationships were seen between the cephalometric and photographic FMA analogous angles in studies by Bittner and Pancherz (11) and de Carvalho Rosas Gomes et al (3). This dissimilarity possibly is due to the direction of intracranial SN line, which showed singular alterations (3).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similar to our study, when comparing the results of FMA and cephalometric Sn-GoMe, the researchers did not find a strong correlation coefficient. On the contrary, powerful relationships were seen between the cephalometric and photographic FMA analogous angles in studies by Bittner and Pancherz (11) and de Carvalho Rosas Gomes et al (3). This dissimilarity possibly is due to the direction of intracranial SN line, which showed singular alterations (3).…”
Section: Discussionmentioning
confidence: 83%
“…Nonethe-less, since the development of the cephalostat and standardization of the radiographic methods, the photography of the face has turned into an auxiliary record for many years. The emphasis was on the objective evaluation of cephalometric radiographs, putting only an objective role for facial photography (3). Cephalometric radiography was innovated by Broadbent and Hofrath in 1931 and thereafter, it has been widely used as a necessary instrument in orthodontic offices for the discussion of malocclusion and vertical skeletal problems, as well as in clinical and research orthodontics by investigators (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen facial measurements were obtained through standardized frontal and lateral facial photographs in accordance with the method described by Scavone . One modification was required for the natural head position, because of the difficulty of some indigenous subjects to look at their own face when in front of the mirror, for cultural reasons.…”
Section: Methodsmentioning
confidence: 99%
“…De Carvalho et al, compared lateral cephalograms with profile photo graphs of 123 subjects and found A'N'B' angle was most effective amongst the other measurements in explaining variability [8].…”
Section: Discussionmentioning
confidence: 99%
“…The method was developed by Sheldon WA and introduced in the field of orthodontics by Stoner MM who compared pre-and post-treatment profiles photographs of 34 patients exhibiting Class II div 1 and 2 and Class III malocclusion with ideal profiles [5,6]. Numerous studies have been conducted on comparing reference distances of soft tissue with that of lateral cephalograms [7][8][9][10]. The reliability of landmarks by superimposing the photograph and lateral cephalogram was evaluated by Philips C et al, [11].…”
Section: Introductionmentioning
confidence: 99%